Interstitial Telomeric Sequences Are Not Preferentially Involved in the Chromosome Damage Induced by the Methylating Compound Streptozotocin in Chinese Hamster Cells - Quiroga, Ivana Yoseli (2013)
The effect of the methylating compound streptozotocin (STZ) on interstitial telomeric sequences (ITSs) was investigated in Chinese hamster ovary (CHO) cells by using peptide nucleic acid-fluorescence in situ hybridization with a pantelomeric probe. Cells were exposed to increasing concentrations of STZ, and chromosomal aberrations were analyzed at the first mitosis after treatment. The frequency of chromosomal aberrations directly involving ITSs increased in STZ-treated cells by a factor of 2.6 (2 mM) and 3.6 (4 mM) when compared with the frequency of these aberrations in control cells (P < 0.05). However, no significant differences were found between control and exposed cells in the percentage of aberrations directly involving ITSs, demonstrating that these repeat regions were not preferentially involved in the chromosome damage induced by STZ. In addition, STZ did not alter telomerase activity, suggesting that this enzyme may not be involved in the induction of chromosomal aberrations by this compound. Environ. Mol. Mutagen. 54:147–152, 2013.